2005
DOI: 10.1158/0008-5472.can-04-2552
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of EBV-Encoded Nuclear Antigen 1–Specific CD4+ Helper and Regulatory T Cells Elicited byIn vitroPeptide Stimulation

Abstract: CD4+ helper and regulatory T (Treg) cells play important but opposing roles in regulating host immune responses against cancer and other diseases. However, very little is known about the antigen specificity of CD4 + Treg cells. Here we describe the generation of a panel of EBV-encoded nuclear antigen 1 (EBNA1)-specific CD4 + T-cell lines and clones that recognize naturally processed EBNA1-P 607-619 and -P 561-573 peptides in the context of HLA-DQ2 and HLA-DR11, -DR12, and -DR13 molecules, respectively. Phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 46 publications
3
62
0
Order By: Relevance
“…Both EBNA1 and LMP1 are known to encode for antigenic peptides that expand IL‐10‐secreting regulatory CD4 + T cells 38, 39. However, no correlations were found between the EBV latency II genes and expression of either CD4 or the regulatory T cell markers IL‐10, lymphocyte‐activation gene 3 (LAG3) and forkead box protein 3 (FoxP3) [ P  = not significant (n.s.…”
Section: Resultsmentioning
confidence: 99%
“…Both EBNA1 and LMP1 are known to encode for antigenic peptides that expand IL‐10‐secreting regulatory CD4 + T cells 38, 39. However, no correlations were found between the EBV latency II genes and expression of either CD4 or the regulatory T cell markers IL‐10, lymphocyte‐activation gene 3 (LAG3) and forkead box protein 3 (FoxP3) [ P  = not significant (n.s.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that these malignancies are able to develop despite the presence of circulating tumor-specific T cells. Secretion of immunosuppressive chemokines and cytokines and the presence of regulatory T cells at the tumor site may contribute to this escape from immune surveillance (21). Immunotherapeutic strategies that enhance the LMP2-specific immune response may overcome this immunosuppressive environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its potential role in the pathogenesis of NPC, EBV also provides a possible target for immunotherapy of NPC, since a limited number of viral genes are expressed in the neoplastic cells, including EBNA1, LMP1 and LMP2 (16,17,19,20). Although EBNA1 appears to be an immunogen for reactivating EBNA1-specific CD4 + T cell clones, the majority of such clones fail to recognize lymphoblastoid B cell lines (LCL) target cells (21). LMP1 has been confirmed to be consistent with its ability to transform rodent fibroblasts, and its target epitopes recognized by virus-specific CTL are easy to mutate (22).…”
Section: Introductionmentioning
confidence: 99%
“…7). Recently, Voo et al (28) reported that EBV-encoded nuclear Ag 1 peptide-reactive Treg cells required cell-cell contact or an unidentified soluble factor (not IL-10 nor TGF-␤) to exert their suppressive activity.…”
Section: Discussionmentioning
confidence: 99%
“…These Treg cells express several characteristic markers such as CD25, glucocorticoid-induced TNF receptor (GITR), and the Forkhead Box P3 (Foxp3) transcription factor (22)(23)(24)(25)(26)(27)(28). Although Foxp3 may be a relatively specific intracellular marker compared with other cell surface molecules, a definitive maker for Treg cells has not been found yet.…”
mentioning
confidence: 99%